Differentiated Instruction in Multicultural Classroom of Primary Years Program in Gandhi Memorial Intercontinental School-Bali - Partami, Indah (Universitas Pendidikan Ganesha, 2019)
A multicultural classroom has significant student’s diversity, especially in terms of language. The similar teaching strategy cannot be generated to cover all students’ needs. Due to that problem, this study aimed at describing how differentiated instruction is planned, implemented, and assessed in multicultural classroom of Primary Years Programme in GMIS Bali, finding out challenges encountered by the PYP’s homeroom teachers in practicing differentiated instruction in multicultural classroom, and analyzing teachers’ perceptions toward differentiated instruction in multicultural classroom. The study employed mixed method. The data were collected through observation, interview, administering the questionnaire, and document study. The finding of this study are; first, teachers were practicing differentiated tasks through content, remedial task, product based on student’s interest and reading buddy program through formative and summative assessment that was conducted in a unit. Second, the main challenge encountered by teachers of GMIS Bali was covering the standards to everyone meanwhile each student has different English proficiency and teachers have limited time for preparing DI. And third, teachers of GMIS Bali were showing positive perception toward DI by their awareness about the concept, implementation, and implication. Thus, this study has an important contribution to teacher’s pedagogical and professional competence and there is a need for further research about how to anticipate the challenges that cannot be filled by the teachers.